Advanced hierarchical nanostructured materials - Zhang, Qiang (Associate Professor of Chemical Engineering); Wei, Fei, 1962- (Weinheim, Germany : Wiley-VCH, Verlag GmbH & Co. KGaA, 2014)
An overview of the recent developments and prospects in this highly topical area, covering the synthesis, characterization, properties and applications of hierarchical nanostructured materials. The book concentrates on those materials relevant for research and development in the fields of energy, biomedicine and environmental protection, with a strong focus on 3D materials based on nanocarbons, mesoporous silicates, hydroxides, core-shell particles and helical nanostructures. Thanks to its clear concept and application-oriented approach, this is an essential reference for experienced researchers and newcomers to the field alike.
4.2.3 Electrospinning Technique4.3 Synthetic Methods for 3-D or Nonspherical Hollow Metallic Micro/Nanostructures; 4.3.1 Hard Template Strategy; 4.3.2 Sacrificial Template Strategy; 4.3.3 Soft Template Strategy; 4.3.4 Template-Free Strategy; 4.3.4.1 Ostwald Ripening; 4.3.4.2 Kirkendall Effect; 4.4 Potential Applications of Hollow Metallic Micro/Nanostructures; 4.4.1 Lithium-Ion Batteries; 4.4.2 Magnetic Properties; 4.4.3 Sensors; 4.4.4 Catalytic Properties; 4.5 Conclusions and Outlook; Acknowledgments; References; Chapter 5 Polymer Vesicles; 5.1 Introduction; 5.2 Vesicle Formation.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed on May 30, 2014).
Keywords: Nanostructured materials; Deformations (Mechanics); Electrospinning; Nanostructured materials; TECHNOLOGY & ENGINEERING -- Nanotechnology & MEMS; Nanostructured materials; Electronic books